2014
DOI: 10.11648/j.ajbls.20140202.11
|View full text |Cite
|
Sign up to set email alerts
|

Serological Screening of TORCH Agents as an Etiology of Spontaneous Abortion in Dhulikhel Hospital, Nepal

Abstract: The role of TORCH infections as a cause of spontaneous abortions is still debatable with conflicting results where geographical variation may play a significant role. This study was undertaken to discover the association of TORCH infections in women with spontaneous abortions by serological testing. The descriptive case control study was conducted from January to December, 2012. A serological evaluation was carried out to determine the presence of Toxoplasma gondii, Rubella, Cytomegalovirus (CMV) and Herpes Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…None of the study has done yet to compare the sensitivity of the ELISA and CLIA. The sensitivity issue could be another reason for this large deviation.In another study done in 2012 at Dhulikhel, Kathmandu University, prevalence rates were estimated as 77.9% for T. gondii, 86.8% for Rubella, 51.9% for CMV and 84.4% for HSV (Acharya et al, 2014). The finding of this study was comparable to our study.…”
Section: Torch Infection Among Hiv Positive Casessupporting
confidence: 87%
“…None of the study has done yet to compare the sensitivity of the ELISA and CLIA. The sensitivity issue could be another reason for this large deviation.In another study done in 2012 at Dhulikhel, Kathmandu University, prevalence rates were estimated as 77.9% for T. gondii, 86.8% for Rubella, 51.9% for CMV and 84.4% for HSV (Acharya et al, 2014). The finding of this study was comparable to our study.…”
Section: Torch Infection Among Hiv Positive Casessupporting
confidence: 87%
“…In Africa and Asia, the reported incidences vary from (0.5%) in Japan to (1.38%) in Ivory Coast, and 1.8% in Taiwan in the presence of a very high rate (90-100%) of preexisting maternal immunity (Kenneson and Cannon 2007;Istas et al,1995). In a study in Nepal, an infection rate of (34%) is found (Acharya et al, 2014;Kumari et al, 2011).…”
Section: Materials and Methods Sample Collectionmentioning
confidence: 99%
“…Toxoplasmosis is an infection by obligate intracellular protozoan parasite Toxoplasma gondii. It is one of the most prevalent chronic infections affecting one third of world's population, [2][3][4] characterized by nonspecific symptoms like fever, malaise and lymphadenopathy. Maternal screening is recommended when fetal abnormalities like hydrocephaly, anatomic abnormalities of the central nervous system, symmetric fetal growth restriction, and nonimmune hydrops are observed.…”
Section: Toxoplasmosismentioning
confidence: 99%